2020
DOI: 10.1007/jhep05(2020)123
|View full text |Cite
|
Sign up to set email alerts
|

E6 motivated UMSSM confronts experimental data

Abstract: We test E 6 realisations of a generic U(1) extended Minimal Supersymmetric Standard Model (UMSSM), parametrised in terms of the mixing angle pertaining to the new U(1) sector, θ E 6 , against all currently available data, from space to ground experiments, from low to high energies. We find that experimental constraints are very restrictive and indicate that large gauge kinetic mixing and θ E 6 ≈ −π/3 are required within this theoretical construct to achieve compliance with current data. The consequences are tw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 80 publications
0
10
1
Order By: Relevance
“…In such conditions, then, the bound from Z 0 → W þ W − is practically the same as from the dilepton searches. Our bounds are slightly lower than in [21], though, as in our case, the inert superpartners are light and take a share of the Z 0 BR. Notice that, in what follows the Z 0 mass is relevant in the DD rates of inert neutralinos, but the corresponding results can easily be scaled to a given Z 0 mass.…”
Section: Simplified E 6 Ssm Modelcontrasting
confidence: 62%
“…In such conditions, then, the bound from Z 0 → W þ W − is practically the same as from the dilepton searches. Our bounds are slightly lower than in [21], though, as in our case, the inert superpartners are light and take a share of the Z 0 BR. Notice that, in what follows the Z 0 mass is relevant in the DD rates of inert neutralinos, but the corresponding results can easily be scaled to a given Z 0 mass.…”
Section: Simplified E 6 Ssm Modelcontrasting
confidence: 62%
“…Hence, such particles may also escape usual SUSY searches. The recent studies have already shown that extending the symmetry and/or particle content can nicely fit the solutions to experimental data [11][12][13]. Moreover excluded regions of the MSSM parameter space can be realized consistent with the experimental results, if one simply considers non-holomophic (NH) terms in the soft supersymmetry breaking (SSB) lagrangian [14].…”
Section: Introductionmentioning
confidence: 65%
“…Whereas in general U(1) models one must either introduce exotic fermion fields, or add three scalar singlets (secluded U(1) models) to cancel all anomalies. This class of models have been explored [75][76][77][78][79][80][81][82] by assuming family-universal U(1) charges for the MSSM fields inspired by the lepton universality of the SM. However, it is also possible to consider sets of U(1) charges in which different families of matter fields can have distinct charges [83].…”
Section: Jhep10(2021)063mentioning
confidence: 99%
“…Indeed, supersymmetric U(1) models were originally motivated by stabilizing the µ−term at the scales consistent with the EW symmetry breaking. This class of supersymmetric models can be motivated by the SUSY grand unified theories (GUTs), since additional U(1) groups can emerge from the breaking of grand unified groups larger than SU(5) such as SO (10) and E 6 , which are extensively explored in [73,79,84,85].…”
Section: Jhep10(2021)063 2 Non-universal U(1) Modelsmentioning
confidence: 99%